Design and Engineering of 3D Collagen-Fibronectin Scaffolds for Wound Healing and Cancer Research - Asadishekari, Maryam (Université d'Ottawa / University of Ottawa, 2018)
Despite our understanding of the importance of the 3D environment on the behaviour of virtually every cell, most studies are still performed within 2D engineered cell culture devices. In this project, the main goal was to design and engineer tunable three-dimensional (3D) extracellular matrix (ECM)-mimicking scaffolds made of collagen and fibronectin (namely the two major building blocks of the ECM) that recapitulate the ECM structural and mechanical properties essential for wound healing and cancer research. Two different methods were implemented to fabricate 3D scaffolds. First, 3D collagen scaffolds with a ‘porous’ structure (fabricated by a previous student via an ice-templating technique) were used. It was shown that, by increasing collagen concentration to 1.25 wt.%, homogenous scaffolds with interconnected pores (needed for cell invasion through the entire scaffold) were obtained. Fibronectin (Fn) was then incorporated using thermal and mechanical gradients to modify protein content and tune scaffolds microarchitecture. The effect of Fn coating of the collagen underlying structure on cell behaviour such as cell adhesion, invasion and matrix deposition was studied. Results showed that overall more cells adhered to Fn-coated scaffolds with respect to pure collagen scaffolds. Furthermore, our findings indicated that cells were also able to sense the conformation of the Fn coating (as assessed by Fluorescence Resonance Energy Transfer, FRET) since they deposited a more compact ECM on compact Fn coating while a more unfolded and stretched ECM was deposited on unfolded Fn coating. Second, 3D more complex physiologically relevant scaffolds with a ‘fibrillar’ structure were fabricated via a cold/warm casting technique. Pure collagen scaffolds were first generated: in cold-cast scaffolds, clear thin and long collagen fibers were observed while warm-cast scaffolds were denser and comprised shorter collagen fibers. The effect of both collagen concentration and casting temperature on scaffolds’ microstructure was studied. Our results indicate a preponderant effect of temperature. We further engineered dual-protein fibronectin-collagen fibrillar scaffolds by incorporating Fn fibers using thermal gradient. Clear Fn fibers were observed in some conditions. FRET assessment of Fn fibers also showed significant difference of Fn conformation. In this more advanced casting technique, cells were initially embedded into the scaffolds, which provided a more homogeneous cell distribution and a better tissue-mimicking setting. In each case, the effect of resulting ECM properties was tested via cell viability assays. Our data indicate that cells were viable after 72 hours, they could proliferate inside the scaffolds and were able to spread in some conditions. Collectively, our 3D ECM-mimicking scaffolds represent a new tunable platform for biological and biomaterial research with many potential applications in tissue engineering and regenerative medicine. Investigating cell behaviour in 3D ECM-mimicking environment will provide valuable insights to understand cancer progression and approaches to limit the progression and ultimately prevent metastasis.
Keywords: Biomaterials; Scaffolds; Collagen; Fibronectin